Dynamics and Anthropisation of Edible Caterpillar Habitats in the Landscape of the Luki Biosphere Reserve, Democratic Republic of the Congo - Ernestine Lonpi Tipi; Médard Mpanda Mukenza; Yannick Useni Sikuzani; Jean-Pierre Messina Ndzomo; Raoul Sambieni Kouagou; François Malaisse; Joseph Lumande Kasali; Damase Khasa; Jan Bogaert (Land, 2025)
The Luki Biosphere Reserve landscape is located in the southwest of the Democratic Republic of Congo. Illicit anthropogenic activities in this landscape have contributed to the degradation of forest massifs, which are habitats for edible caterpillars. Accordingly, based on five Landsat images covering 2004–2024 period, we analysed the dynamics of edible caterpillar habitats in the Luki Biosphere Reserve, its periphery, and the landscape. The study was complemented by the calculation of class area, number of class patches, dominance, and the disturbance index. The results show that fragmentation and attrition have caused forest areas to decline by 46.13%, 21.17%, and 23.54% in the Reserve, its periphery, and at the landscape level, respectively. The dynamics of caterpillar habitats are reflected in the replacement of forest and fallow land by savannah. The level of disturbance has thus risen from 0.3 to 1.6 in the Reserve, from 2.5 to 13.9 in the periphery, and from 2.0 to 9.2 on a landscape scale. These results are mainly attributed to the expansion of agricultural land. Our observations imply an extent of disturbance in caterpillar habitats that might cause their scarcity, and strongly indicate the need for promoting effective strategies for preserving and restoring forest ecosystems in this landscape.